2016
DOI: 10.1177/2050312116682253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-intensity training on endothelial function in patients with cardiovascular and cerebrovascular disease: A systematic review

Abstract: Objectives:Exercise improves endothelial dysfunction, the key manifestation of cardiovascular and cerebrovascular disease, and is recommended in both cardiovascular and cerebrovascular rehabilitation. Disagreement remains, however, on the role of intensity of exercise. The purpose of this review was to gather current knowledge on the effects of high-intensity training versus moderate-intensity continuous exercise on endothelial function in cardiovascular and cerebrovascular patients.Methods:A systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…The absolute magnitude of the increase in risk associated with vigorous exertion is extremely small, and the overall risk of sudden death was not increased in association with increasing frequency of vigorous exercise 58. Even sometimes, high-intensity endurance training is safe and highly relevant in patients with CVD59 if there is close monitoring during the training.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute magnitude of the increase in risk associated with vigorous exertion is extremely small, and the overall risk of sudden death was not increased in association with increasing frequency of vigorous exercise 58. Even sometimes, high-intensity endurance training is safe and highly relevant in patients with CVD59 if there is close monitoring during the training.…”
Section: Discussionmentioning
confidence: 99%
“…As recommended by guidelines, authors chose mostly a moderate training intensity, although guidance parameters varied between the studies. A meta-analysis recently showed that high-intensity training improves endothelial function in patients with cardiovascular disease [ 24 ], hereby raising the question whether it might be a time-efficient alternative or addition in NOCAD patients. Furthermore, training strategies like skiing appear to have a beneficial effect on endothelial health, which might broaden the recommended exercise spectrum, at least in alpine regions [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and oxidative stress are strongly associated with the progression of endothelial dysfunction; in turn, the latter is the physiopathological substrate of several cardiovascular diseases with high impact on mortality indices such as myocardial infarction, cerebrovascular disease, and chronic renal failure [ 33 , 34 , 35 ]. Thus, treatments to control both conditions are emerging as key therapies against these high-impact diseases [ 1 ].…”
Section: Discussionmentioning
confidence: 99%